PENERAPAN STRATEGI PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 019 KAMPUNG DAGANG KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Rahmadeni, Sarmudiah; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was motivated by the facts that occurred in class IV SDN 019 Kampung Dagang, who showed symptoms of the students did not master the material science lessons have been learned. The problem of this research is